2018
DOI: 10.1126/scitranslmed.aar6759
|View full text |Cite
|
Sign up to set email alerts
|

CD32 is expressed on cells with transcriptionally active HIV but does not enrich for HIV DNA in resting T cells

Abstract: The persistence of HIV reservoirs, including latently infected, resting CD4+ T cells, is the major obstacle to cure HIV infection. CD32a expression was recently reported to m ark CD4+ T cells harboring a replication-competent HIV reservoir during antiretroviral therapy (ART) suppression. We aimed to determine whether CD32 expression marks HIV latently or transcriptionally active infected CD4+ T cells. Using peripheral blood and lymphoid tissue of ART-treated HIV+ or SIV+ subjects, we found that most of the cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
104
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(131 citation statements)
references
References 53 publications
25
104
2
Order By: Relevance
“…Indeed, apart from CD32a, a low affinity receptor for immunoglobulin G Fc fragment recently described as a specific biomarker for CD4+ T cell HIV-reservoir [102], there is a crucial lack of specific biomarkers for latently infected cells. Indeed, even the CD32a marker is a matter of controversy with several papers challenging with their finding [103,104]. However, a recent communication at the 2018 Frontier of Retrovirology congress corroborated the results of the group of Benkirane by showing with another approach that indeed CD32+CD4+ T cells are enriched in HIV-1 DNA [105].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Indeed, apart from CD32a, a low affinity receptor for immunoglobulin G Fc fragment recently described as a specific biomarker for CD4+ T cell HIV-reservoir [102], there is a crucial lack of specific biomarkers for latently infected cells. Indeed, even the CD32a marker is a matter of controversy with several papers challenging with their finding [103,104]. However, a recent communication at the 2018 Frontier of Retrovirology congress corroborated the results of the group of Benkirane by showing with another approach that indeed CD32+CD4+ T cells are enriched in HIV-1 DNA [105].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…38 It has been also proposed that HIV reservoirs persist in long-lived stem cell memory CD4 + T cells 39 and in CD4 T cells expressing CD32, 40 although these results are controversial. 41,42 Consistent with the fact that HIV targets lymphoid organs, follicular helper (TFH) cells, a subset of memory CD4 T cells, which are mainly localized in germinal centers, have been known to be infected by both HIV and simian immunodeficiency virus (SIV). [43][44][45][46][47][48][49] Recently, analyses of viral sequences in the plasma of viremic controllers have indicated that viral sequences are closer to HIV DNA sequences observed in TFH cells from peripheral LNs, than those observed in CD4 T cells derived from peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggesting that CD32a (a low-affinity IgG receptor not generally expressed on T cells 10 ) was a specific marker for latent HIV infection 11 was initially supported by studies showing that CD32 may be found on cells that are transcriptionally active, and was associated with HIV DNA levels in some patients. [12][13][14][15][16][17][18][19] However, the finding that CD32 co-expression with CD4 is predominantly due to T-cell-B-cell doublets 17 likely undermines the argument that CD32 is a definitive marker of latency.…”
Section: Introductionmentioning
confidence: 99%